2019
DOI: 10.1093/ofid/ofz312
|View full text |Cite
|
Sign up to set email alerts
|

Positive Impact of a Point-of-Care Molecular Influenza Test in the Emergency Department During the 2017–2018 Seasonal Influenza Epidemic

Abstract: During the 2017–2018 flu epidemic, the point-of-care Alere-i (n = 72) and reverse transcription polymerase chain reaction (n = 106) tests were compared. Patients in the point-of-care group were administered oseltamivir significantly more rapidly (9 hours vs 23 hours), they spent less time in the emergency department, and they had lower rates of antibiotic administration and hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…With respect to ED-LOS, the systematic reviews noted no overall decrease in ED-LOS. However, in the viral influenza group, 7 studies 3,4,11,14,19,20,22 showed a significant decrease in ED-LOS, with 4 showing no significant change in ED-LOS. 6,12,18,21 The remaining 10 studies 5,[7][8][9][10]13,[15][16][17]23 did not report any findings related to ED-LOS.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…With respect to ED-LOS, the systematic reviews noted no overall decrease in ED-LOS. However, in the viral influenza group, 7 studies 3,4,11,14,19,20,22 showed a significant decrease in ED-LOS, with 4 showing no significant change in ED-LOS. 6,12,18,21 The remaining 10 studies 5,[7][8][9][10]13,[15][16][17]23 did not report any findings related to ED-LOS.…”
Section: Resultsmentioning
confidence: 87%
“…As indicated in Tables 1 through 3, a variety of additional significant findings were identified on a case-by-case basis, but it was not clear if they actually improved patient outcomes. Of note, several studies did show decreased admissions 4,7,11,[13][14][15]19 and decreased hospital stays, § which could a priori reflect improved outcomes. However, inpatient LOS is not a typical reason for requesting ED-POCT.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies on the effectiveness of rapid testing for respiratory viruses have primarily focused on influenza and have evaluated impacts on therapeutic decision-making and reductions in ED and hospital lengths of stay. [ 9 , 10 , 16 ] To our knowledge, this study is unique in that it is the first to evaluate the clinical effectiveness of rapid testing for SARS-CoV-2 and because it focuses on both infection risk exposure time and resource savings. Our demonstration that a relatively small number of rapid tests, if properly targeted, can be used to drive large decreases in time that patients spend under investigation for infectious disease in the hospital setting is novel.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the effectiveness of rapid testing for respiratory viruses have primarily focused on influenza, and have evaluated impacts on therapeutic decision-making and reductions in ED and hospital lengths of stay [9,10,16]. To the authors' knowledge, this study is unique in that it is the first to evaluate the clinical effectiveness of rapid testing for SARS-CoV-2, and because it focuses on both risk exposure time and resource savings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation